Pengembangan Lembar Kerja Siswa (LKS) Melalui Problem Based Learning (PBL) Berbasis Budaya Pamona Ditinjau dari Keaktifan Siswa SMA - Fitrianti, fitrianti; Aditia, Iccal (Supermat : Jurnal Pendidikan Matematika, 2023)
This research aims to develop worksheets using the Pamona culture-based PBL model to increase student activity. This development research was carried out in class The aim of this research is to produce and validate the feasibility of student worksheets through problem based learning on SPLTV material at SMA Negeri Harmoni. The data analysis technique used is student worksheet development data as well as feasibility data and student assessment responses. The results of this research show that the Pamona Culture-based worksheet on SPLTV material is viewed from the media aspect in the "Fine" category, the material aspect in the "Fine" category, the results of small group trials obtained a percentage of 33% in the "Very Feasible" category and 67% in others. in the "Feasible" category as well as large group trials, a percentage of 19% was obtained in the "Very Eligible" category and another 81% in the "Appropriate" category as teaching materials.